2015
DOI: 10.3386/w21144
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disability Benefits on Labor Supply: Evidence from the VA's Disability Compensation Program

Abstract: Combining administrative data from the U.S. Army, Department of Veterans Affairs (VA) and the U.S. Social Security Administration, we analyze the effect of the VA's Disability Compensation (DC) program on veterans' labor force participation and earnings. The largely unstudied Disability Compensation program currently provides income and health insurance to almost four million veterans of military service who suffer service-connected disabilities. We study a unique policy change, the 2001 Agent Orange decision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Two of these studies found that the expansion of the US Veterans’ Affairs Disability Compensation program (VDC) to include people with diabetes was associated with a decline in employment amongst male veterans. Autor et al (2015) found that 18 percent of all newly eligible veterans left the labour force, while Autor and Duggan (2007) concluded that the policy change was associated with a significant, and substantial, reduction in employment among veterans [ 19 , 20 ]. Autor and Duggan (2003) also found that the use of a broader definition of disability in the US Disability benefit programme from 1984 was associated with reduced employment of low educated older men and women, but did not have the same effect on higher educated groups [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these studies found that the expansion of the US Veterans’ Affairs Disability Compensation program (VDC) to include people with diabetes was associated with a decline in employment amongst male veterans. Autor et al (2015) found that 18 percent of all newly eligible veterans left the labour force, while Autor and Duggan (2007) concluded that the policy change was associated with a significant, and substantial, reduction in employment among veterans [ 19 , 20 ]. Autor and Duggan (2003) also found that the use of a broader definition of disability in the US Disability benefit programme from 1984 was associated with reduced employment of low educated older men and women, but did not have the same effect on higher educated groups [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Relative risks of the policy effects were calculated for 39 of the 40 results. The relative risk could not be calculated for one study as the results were presented per 1 percentage point increase benefit enrolment, rather than as the overall policy effect [ 20 ]. Only two studies investigated effects by socioeconomic group and therefore we could not analyse differences in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%